Tautological formal explanations: does prior knowledge affect their satisfiability? - Aslanov, Ivan; Guerra, Ernesto (Frontiers in Psychology, 2023)
It is known that formal explanations with categorical labels are more satisfying than explicit tautologies. However, would they still be more satisfying if they are implicitly tautological themselves? In two experiments, we compared the degree of satisfaction between tautological formal explanations, explicit tautologies, and proper regular explanations. Additionally, we examined whether participants knew the correct definitions for the labels used in the formal explanations. Finally, we asked whether cultural and linguistic differences can play a role in the treatment of formal explanations with categorical labels. To this end, the first experiment involved Chilean students (N=50), and the second experiment involved Russian students (N=51). It was found that formal explanations, despite their intentional tautology, were still rated as more convincing compared to explicit tautologies (but less convincing than proper regular explanations). Furthermore, this effect did not depend on participants' previous knowledge (the label''s definitions) or linguistic and cultural background. Taking all this into account, we consider this effect as a relatively universal psychological phenomenon and relate our findings to existing theories of formal explanations.